Long-term aerobic exercise improves learning memory capacity and effects on oxidative stress levels and Keap1/Nrf2/GPX4 pathway in the hippocampus of APP/PS1 mice - Wang, Shiyan; Zhou, Ye; Wu, Yucheng; Lang, Yali; Mao, Yajun; Pan, Guoyuan; Gao, Zhenzhen (Frontiers in Neuroscience, 2024)
ObjectiveTo examine the effects of long-term aerobic exercise on oxidative stress and learning memory ability of APP/PS1 mice, focusing on the hippocampal Keap1, Nrf2, HO-1, and GPX4 proteins.MethodsThirty APP/PS1 double transgenic AD mice were randomly divided into three groups: model group, short-term exercise group, and long-term exercise group, with 10 mice in each group. Male non-transgenic mice of the same age served as the control group. The groups underwent swimming training for 6 weeks and 12 weeks, respectively. After the intervention, cognitive abilities were assessed using the Morris water maze test. Hippocampal tissue samples were analyzed for changes in superoxide dismutase (SOD) activity and malondialdehyde (MDA) content. ROS expression was observed using dihydroethidium probe, and Keap1, Nrf2, HO-1, and GPX4 protein levels were detected by Western blot analysis.ResultsAerobic exercise significantly reduced the escape latency and increased both the time spent in the target quadrant and the number crossing the platform compared to the model group (p < 0.05). In the hippocampus, aerobic exercise significantly reduced the MDA content, while significantly increased SOD activity (p < 0.05). The level of ROS in the hippocampal region was significantly reduced by aerobic exercise (p < 0.05), with decreased Keap1 protein expression of and increased Nrf2, HO-1, GPX4 protein expression (p < 0.05).ConclusionAerobic exercise enhances memory and learning abilities, improves cognitive function, and reduces the oxidative stress levels in the hippocampus of AD mice, which involves in the activation of Keap1/Nrf2/GPX4 pathway.